National and Cultural Specificity of Zoomorphic Figurative Means in H. Hosseini's Novel "The Kite Runner" - Ravshanovna, Bakhronova Zulfiya; Kahhorovna, Turakulova Dilafruz; Sharafovna, Sharapova Gulshan; Yasaviyevna, Shigabutdinova Dina (International Journal on Integrated Education, 2023)
The article deals with zoomorphic figurative means in H. Hosseini's novel "The Kite Runner". The scientific novelty of the study is because the functioning of zoomorphisms is studied based on the work of a bilingual writer within the framework of a cognitive-discursive approach. The study showed that the functioning of zoomorphisms in this novel is more variable, their use is characterized by an expansion of the scope of their meanings, as well as a restructuring of associative links, which confirms the existing thesis about a more flexible and dynamic creative consciousness of a bilingual writer.